(untitled) (Scientific journal of the Fergana State University, 2026)
This article provides a broad overview of the theoretical foundations of the modernization of the higher medical education system. It analyzes the scientific and theoretical foundations of person-centered and competency-based approaches, pedagogical mechanisms, digital technologies, and interactive teaching methods in medical education. In particular, the issues of improving the methodology for developing student knowledge, introducing modern pedagogical technologies, and developing practical skills through activity-oriented approaches in medical education are studied in depth. The article proposes new approaches aimed at improving the quality and efficiency of higher medical education.